Contributor factors for psychological well-being: a qualitative study of teachers' perspective in Malaysia - Chan, Siaw Leng; Adam Assim, Mohd Ibrani Shahrimin; Lim, Fong Peng (Human Resource Management Academic Research Society, 2021)
Universally, the educational systems are undergoing restructuring and transformations. The role of teachers has increased following this reformation and experiencing growing pressure to perform. Given that the nature of the teaching profession is both challenging and rewarding, it is vital to understand teachers' psychological well-being to support the mental health of this population. This study aimed to understand better the subjective perspectives regarding the contributor factors to psychological well-being among teachers. A consensual qualitative research approach was adopted in this study by collecting data through in-depth, semi-structured interviews. Interviews are used to understand the participants' narrative descriptions in-depth and uncover the meaning of their experiences, beliefs, and values. Seven Malaysian teachers were recruited from local school settings through purposive sampling. Data analysis involved an open-coding process in deriving themes from the participants' responses. Findings revealed five themes that indicate contributor factors for psychological well-being: positive attitudes, spiritual convictions, family and friends' support, personal growth, and personal responsibility. The practical implications of teachers' psychological well-being, mental health and psychotherapy practice, and future research were also discussed in this work.